(untitled) (Scientific journal of the Fergana State University, 2025)
This article will consider the issues of improving the methodology for preparing students for scientific and pedagogical activities. In their preparation for pedagogical activity, students need not only to master theoretical knowledge, but also to develop practical skills. The article presents new methods and approaches for students to effectively teach scientific and pedagogical activities. The role of pedagogical practices in the preparation for scientific and pedagogical activity, the use of innovative pedagogical technologies, practical training and the role of methodological approaches in the development of creativism are highlighted. New methodological approaches and methods play an important role in activating students in the educational process and developing their pedagogical skills.